A Pragmatic Analysis on the Speech Acts Used by Three English Teachers of SMP, SMA, and SMK during Online Teaching and Learning Process - Nur Shafiera; Fatchul Mu’in; Nanik Mariani; Noor Eka Chandra (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
This study aims to analyze the speech acts used by three English teachers of SMPIT Nurul Ikhwan Nagan Raya, SMA Tunas Luhur, and SMKN 2 Payakumbuh during online teaching and learning process. This research was descriptive-qualitative. The data were the subjects’ utterances obtained by observations on six online learning videos from YouTube. It was transcribed into the written form, selected to fit the study’s objective, recorded into the datasheets, interpreted, and analyzed using speech acts theory. The practice of triangulation was used by asking the expert to check data validity. The result showed that declarative locutionary act was mainly used in representatives to utter some explanations of the materials. Directive and representative illocutionary acts were dominantly used. Questioning act of directive used mostly to allow the students to be active and check their comprehension. Explaining and informing of representative were used frequently to transfer the materials and tell certain facts to the students. Perlocutionary act student(s): learn something and do something were primarily occurred. Student(s): learn something mainly occurred when performed explaining and informing of representative resulted to students knew/understood the given explanations and information. Perlocutionary act student(s): do something mainly occurred when questioning and commanding of directive resulted in students giving the answers and doing as commanded. The subjects’ ways in expressing speech acts were quite different since having different background and culture. They used Bahasa Indonesia than English in performing speech acts. It is suggested that the teachers should use English more than Bahasa Indonesia when teaching English. Keywords: Pragmatics, Speech Act, Utterance, Teacher, Online Teaching and Learning, Online Classroom Interaction, Online Learning Video